Institutionalization of Liturgics in the Early Modern Period - Novotný, Vojtěch (Karolinum, 2025)
The monograph traces the processes by which liturgics emerged as an independent institutionalized theological discipline. It proceeds in six steps. The first clarifies the starting points on which the study of liturgy in the early modern period was based (Thomas Aquinas, Melchior Cano, the Reformation, the Counter-Reformation, the magisterium, the catechisms). The second is devoted to the terminology by which the study of liturgy was designated (liturgia, liturgica, de liturgia, de caeremoniis, de ritibus, scientia rituum, scientia liturgica, theologia liturgica). The third provides evidence of the teaching of ritual and liturgics in forms that preceded the institutionalization of this science (liturgical formation, liturgics within polemical theology, moral theology, canon law, positive theology, and as a separate branch of science). The fourth focuses on the first academies and departments of liturgics (Roma, Coimbra) and how the discipline was conceived there. The fifth studies the emergence of liturgical departments in the Habsburg monarchy (1750s), and the sixth how liturgy was temporarily and partially absorbed into pastoral theology in the Central European area (1770s). The research is based on deep heuristics of contemporary texts and takes care to carefully document the findings.
Keywords: Religionistika